2015
DOI: 10.5539/gjhs.v8n2p77
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Multidimensional Expectation Questionnaire for Thalassaemia Major Patients

Abstract: Nowadays, thalassaemia major (TM) patients are surviving into mature young adulthood; however, no published instrument exists to measure the expectations’ dimensionality among older TM patients in their thirties. This study seeks to validate a novel multidimensional expectation questionnaire suitable for TM patients (MEQ-TMP) reaching their fourth decade of life. In order to establish the psychometric properties of the instrument, data analysis was carried out. The principal component analysis revealed four co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The majority of patients are employed or retired, while the unemployment rate is 8.2%. In a study from Greece [26], a group of 109 adult thalassaemia patients had a similar rate of paid employment (77%), while a higher percentage, 23%, were unemployed, consistent with the country's general unemployment rate. Overall, there are very few recent publications dealing with the issue of employment in thalassaemia patients and the comparisons are difficult due to very different social and cultural environments.…”
Section: Social Aspectsmentioning
confidence: 72%
See 2 more Smart Citations
“…The majority of patients are employed or retired, while the unemployment rate is 8.2%. In a study from Greece [26], a group of 109 adult thalassaemia patients had a similar rate of paid employment (77%), while a higher percentage, 23%, were unemployed, consistent with the country's general unemployment rate. Overall, there are very few recent publications dealing with the issue of employment in thalassaemia patients and the comparisons are difficult due to very different social and cultural environments.…”
Section: Social Aspectsmentioning
confidence: 72%
“…Cultural similarities in terms of marriage practices can be compared between Cyprus and Greece or Italy. In the Greek study [26], 36.7% of patients were married, very similar to the Cypriot group, while 52.9% were unmarried or divorced (in the Cypriot group these categories account for 49.3%, and if cohabitation is added then 51.5% are accounted for, almost identical proportions). In an international study conducted by the ICET-A group, which studies mainly endocrinological complications of thalassaemia [27], in a thalassaemia population numbering 966 (consisting of both regularly transfused and non-transfusion-dependent patients from both Europe and Asia, including Cyprus), only 24.8% were married or cohabiting; in both the current study and in the ICET-A study, among adult Cypriot patients, over 50% had fulfilled this life ambition.…”
Section: Social Aspectsmentioning
confidence: 88%
See 1 more Smart Citation
“…This topic needs further research and could be the subject of a completely new research, as indicated in the section on suggestions for further research (see Section 5 for details). Figure 3 presents the learners' expectations of the educator as they emerged from the thematic analysis of the interview data: According to Georgogiannis (2010), Koutelekos and Chaliasos (2014), there are different expectations in terms of quality, which can be divided into positive and negative ones. The first category includes those who hope for success, while the second category includes those who are fearful of success.…”
Section: Resultsmentioning
confidence: 99%
“…When success is part of these expectations, they are called success expectations and have a positive connotation, whereas when there is a fear of failure, they are called negative expectations with a clearly negative connotation. In the first case, individuals may improve their performance, while, in the second case, they may become weaker, making wrong choices (Georgogiannis, 2010;Koutelekos & Chaliasos, 2014). There are many different factors that influence and shape expectations (Sofitsi, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%